Sites and Memory Transmissions: Feminist Articulations, Past and Present, Remembering Political and Patriarchal Violence in Chile (Palimpsesto, 2026)
This paper analyzes feminist memory practices in Chile that recall political and patriarchal violence from both the past and present. Despite women’s central role in resisting the civic-military dictatorship (1973-1990), their political agency remains largely erased from official memory. Through an examination of the material and symbolic expressions of three sites of memory — cueca sola, arpilleras, and monuments — this study explores memory transmission practices that are performed in the present.
Keywords: Dictatorship; Patriarchal violence; Political violence; Memory transmissions; Sites of Memory